2004
DOI: 10.1136/jcp.2003.015735
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific multiple ulcers of the small intestine unrelated to non-steroidal anti-inflammatory drugs

Abstract: Aim: Non-steroidal anti-inflammatory drug (NSAID) enteropathy is a cause of chronic blood and protein loss from the intestine. The aim of this investigation was to compare NSAID enteropathy with enteropathy not related to chronic NSAID use. Patients/Methods: During the period 1967-97, 12 cases of non-specific small intestinal multiple ulcers were laparotomised because of chronic and persistent blood loss for a prolonged period. The clinical features before and after surgery, and the small intestinal lesions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 23 publications
3
46
2
1
Order By: Relevance
“…Although small intestinal ulcers unrelated to use of NSAIDs or enteric-coated drugs are uncommon, a number of such patients have been reported (1). cPLA 2α deficiency may be considered in the molecular differential diagnosis of such ulcers, particularly those with onset early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Although small intestinal ulcers unrelated to use of NSAIDs or enteric-coated drugs are uncommon, a number of such patients have been reported (1). cPLA 2α deficiency may be considered in the molecular differential diagnosis of such ulcers, particularly those with onset early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Only about fifty cases of CMUSE have been published so far (9,33,34,37,46,42) but this entity has probably been considerably underdiagnosed or misdiagnosed, mostly with Crohn's disease and non-steroidal anti-inflammatory drugs (NSAIDs) induced enteropathy. Perlemuter et al (37) reported 12 cases of CMUSE hospitalised between 1965 and 1993.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on an unusual form of enteropathy of unknown etiology, referred to as chronic nonspecific multiple ulcers of the small intestine (CNSU), which is characterized by chronic blood and protein loss through persistent small intestinal ulcers [4][5][6]. Although this rare but distinct clinicopathologic condition was initially reported in the Japanese literature by Okabe and Sakimura [7], the term ''nonspecific'' in its nomenclature which refers to the nonspecific histology of the ulcers has occasionally led to the misinterpretation of the disease as any condition with small intestinal ulcers of undetermined etiology.…”
Section: Introductionmentioning
confidence: 99%